The Role of Self-Esteem as A Mediator in The Influence of The Coach–Athlete Relationship on Achievement Motivation Among Young Athletes on Sports Schools - Kusnanto, Setyo Aji; Latifah, Melly; Hastuti, Dwi (Jp.jok (Jurnal Pendidikan Jasmani, Olahraga dan Kesehatan), 2025)
This study aims to analyze the influence of the coach-athlete relationship and self-esteem on achievement motivation. The research method used is quantitative, with data collected from 208 young athletes. The analysis was conducted using Structural Equation Modeling (SEM-PLS). The results indicate that the coach-athlete relationship falls within the moderate to high range, reflecting positive interaction and practical involvement. The self-esteem of young athletes is also rated as moderate to high, suggesting a positive self-perception and sense of ability. Achievement motivation is clearly evident, showing a strong drive to succeed; however, one dimension, creativity, requires improvement. Structural analysis revealed significant positive relationships between the coach-athlete relationship and self-esteem (β = 0.399) and achievement motivation (β = 0.298). Both relationships were found to be substantial, both directly and indirectly through self-esteem, with a total effect of 0.512. Furthermore, self-esteem directly influences achievement motivation (β = 0.537). These findings confirm that positive interpersonal relationships and high self-esteem are key factors in motivating young athletes to achieve.